Pemanfaatan Air Tanah Dangkal untuk Irigasi Padi Menggunakan Pompa Berbahan Bakar LPG - Agus Haryanto; Suharyadi Suharyadi; Budianto Lanya (PERTETA, 2017)
AbstractThe objective of this study was to evaluate performance of LPG-fueled single cylinder pump enginein utilizing shallow groundwater for rice field irrigation. Research was conducted in Baktirasa Village, Subdistrict of Sragi, Regency of South Lampung during planting session of September–December 2015 by observing and analyzing technical and economical performance of LPG-fueled pump engine. Observation was performed on the depth of groundwater before and after pumping, pumping duration, discharge, LPG consumption, and depth of standing water. Irrigation cost was evaluated using local prices for installation and manpower. Results of the research showed that shallow groundwater is potential to be explored as asource of paddy field irrigation. Depth of water table was substantially low at 3.41 m and decrease to 4.83m after continuous pumping for about 6.5 hours. The LPG-fueled pump engine worked smoothly at an average gas consumption of 0.464 kg/h with a field capacity of 0.0190 ha/h and a discharge rate of 14.58 m3/h. The distribution uniformity of 92.28% was achieved with average depth of standing water of 4.12 cm. The cost of irrigation operation was IDR 226,875.23/ha, lower than leasing one (IDR 400,000.00 /ha).AbstrakPenelitian ini berujuan untuk mengevaluasi kinerja mesin pompa satu silinder berbahan bakar LPG dalam memanfaatkan air tanah dangkal untuk irigasi sawah pada musim kering. Penelitian dilakukan di Desa Baktirasa, Kecamatan Sragi, Lampung Selatan dengan menganalisis kinerja teknis dan ekonomi penggunaan pompa berbahan bakar LPG pada musim tanam September–November 2015. Pompa irigasi 4.9 hp diuji sebanyak lima kali pada lima petak sawah (masing-masing 1250 m2). Parameter yang diamati meliputi kedalaman air tanah sebelum dan sesudah pengoncoran, lama pengoncoran, debit pompa, konsumsi LPG, tinggi genangan air, dan keseragaman distribusi (DU). Biaya irigasi dihitung berdasarkan harga setempat untuk pemasangan sumur dan upah kerja. Hasil penelitian menunjukkan bahwa air tanah dangkal di Desa Baktirasa berpotensi untuk dikembangkan sebagai sumber irigasi. Kedalaman air tanah cukup rendah, yaitu 3.41 m sebelum pemompaan dan turun menjadi 4.83 m setelah pemompaan selama sekitar 6.5 jam terus-menerus. Pompa berbahan bakar LPG bekerja dengan baik dengan kapasitas 0.0190 ha/jam pada debit 14.58 m3/jam, dan konsumsi LPG 0,464 kg/jam. Ketinggian genangan rata-rata 4.12 cm dengan DU 92.28%. Biaya irigasi adalah Rp 226,875.23/ha per sekali oncoran, lebih rendah daripada sewaRp 400.000,00/ha.